An Analytical Study of Arabic Language and Social Studies Textbooks for the Intermediate Stage - Mousa, Dr. Firas Jasim Mousa (Sulaimani Journal for Humanities, 2026)
The aim of this research is to identify the national values embedded in the content of Arabic language and social studies textbooks prescribed for first, second, and third intermediate school students in Iraq. This is to examine their adequacy in developing national values among these students, given the importance of this aspect in protecting the individual, society, and the state as a whole from intellectual deviations and negative behaviors, thereby ensuring the building of a prosperous society. To achieve the research objective, a questionnaire was developed to analyze the content of the aforementioned books, based on a list of national values systems identified based on previous research, studies, and scholarly literature, and then peer-reviewed. Among the most important findings is the presence of (62) national values in all Arabic language textbooks and (90) national values in all social studies textbooks in the political, economic, social, and global fields, with varying levels of presence depending on grades, subjects, and topics. With these percentages and observations, a proposed vision for developing the aforementioned books was presented, the most important of which are: 1. Defining the general and specific objectives of teaching Arabic language and social studies textbooks in light of the national values system. 2. Form a specialized committee of experts, consultants, students, and a representative sample of students and parents to support the current curriculum development committees in submitting proposals to develop Arabic language and social studies textbooks in the field of developing national values. 3. Develop teaching strategies specific to teaching national values topics. 4. Establish a methodological and scientific standard for determining national values topics for Arabic language and social studies textbooks. 5. Respect students' perspectives on their own national values and strive to correct their misconceptions using appropriate methods.
Keywords: national values; curricula; Arabic language; social studies